APPLICATION OF SPATIAL ANALYSIS OF DENGUE HEMORRHAGIC FEVER RISK FACTORS IN TAMAN DISTRICT MADIUN - Riyani Dwi Rivyantanti; Nur Fitriana Arifin; Mursid Rahardjo; Yusniar Hanani Darundiati (Dian Nuswantoro Semarang, 2016)
DHF often causes outbreaks and closely related to the environment. Dengue incidence in the Madiun City increase continuously and the highest incidences occurred in Taman Sub District with IR reached 108.4 per 100,000 population. This research has purpose to analyze the spatial relationship between environmental and behaviors factors with the incidence of Dengue Hemorrhagic Fever (DHF) using Geographic Information System (GIS) in the Taman Sub District of Madiun City. This was an observational analytic research applying case control design. In this research, the sample groups were case sample and control sample. The total members of case and control were 40 members in every group.The case samples were DHF patients from January to May 2015 who living in Taman sub district and the case control were the neighbors who were not infected by DHF. Data were analyzed in univariate and bivariate using Chi Square and spatial analysis using ArcMap. Univariate analysis showed 76.2% risk oftemperature, 18.8% risk of humidity, 75% of high population density, 100% risk altitude, 72,5% ABJ & HI-risk, 31,2% risk CI, 31,2% poorknowledge, 31,2% poor attitude,42,5% poorpractice. This research found that there was a association between the ABJ (p=0,001), HI (p=0,001), CI (p=0,054), and practice (p=0,003) and the dengue case. There was no a relationship between temperature (p=0,599), humidity (p=1,000), population density (p=1,000), knowledge (p=0,335), attitude (p=1,000) with dengue case, while for altitude obtained homogeneous. Mapping the incidence of DHF showed the proportion of a greater dengue incidence was found in the region which was has an average risk temperature, high overcrowding, ABJ & HI-risk, as well as poor of attitudes and practices. Therefore, spatial analysis showed that ABJ & HI-risk and poor PSN practices affected the increase of dengue incidence in Taman sub districts.Keywords: DHF, environmental factors, behavioral factors, spatial analysis